MANAJEMEN PEMBIAYAAN DALAM MENINGKATKAN PENGELOLAAN PENDIDIKAN (Analisis Deskriptif di MTs Roudlatul Falah Desa Sitiluhur Gembong Pati dan SMPN 1 Juwana Pati) - Moch Noor Efendi; Ulil Albab (PASCASARJANA UNISNU, 2019)
AbstractThis article describes financial management in improving education management in schools and madrasahs. The results found include: first, the feasibility of infrastructure, facilities, human resources, as well as facilities and infrastructure because the availability of qualified financing at SMP Negeri 1 Juwana, Pati is directly proportional to the quality of education. Regular students achieve academic and non-academic achievements. Many of the graduates of SMP Negeri 1 Juwana are also scattered in high schools which are in the favorite category; Secondly, high motivation from various elements in MTs Roudlatul Falah, Sitiluhur Village, Gembong District, Pati, especially school principals and educators also has a major effect on the quality of education. Given, a number of madrasah graduates are also able to compete to enter secondary schools which are classified as favorites.Keywords: financing management, education